Translation and democracy in the post-Prevent English classroom - Rashi Rohatgi (University of Aberdeen, School of Education, 2019)
Teachers of literature have lately been asked explicitly to impart national pride. This agenda competes with multiple priorities, one of which is to engage minority students by exposing them to texts in which they can see themselves. Exposure, however, is just the beginning of what teachers can offer as we attempt to balance calls to impart national pride with current pedagogy and personal ideals. This paper uses a cosmopolitan but monocultural school - 99% South Asian Muslim - as a case study to assert that a multicultural education can work towards all of these aims.